Entrepreneurship As Strategy: Competing on the Entrepreneurial EdgeEntrepreneurship As Strategy: Competing on the Entrepreneurial Edge, edited by MeyerG. Dale and HeppardKurt A.. Thousand Oaks, CA: Sage, 2000. - Michael, Steven C. (Academy of Management Review, 2001)
To further our understanding of the entrepreneurial function, editors G. Dale Meyer and Kurt A. Heppard, of the book “Entrepreneurship As Strategy: Competing on the Entrepreneurial Edge,” invited several strategy “superstars” to bring their talents and their theories to bear on the entrepreneurial function, in collaboration with a doctoral student in entrepreneurship. The result is six essays plus an introduction. The unifying theme of the book is to uncover, for firms large and small, the components of an entrepreneurial dominant logic. Although the perspective of each team of authors is different, broadly speaking, two components emerge across the chapters. The first involves a focus on the development of the dynamic core competency of inventing new products faster or better than others. The second component involves development of structures to support this competency.